2020
DOI: 10.1111/bjh.16741
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and pathological characteristics of peripheral T‐cell lymphomas in a Spanish population: a retrospective study

Abstract: We investigated the clinicopathological features and prognostic factors of patients with peripheral T-cell lymphoma (PTCL) in 13 sites across Spain. Relevant clinical antecedents, CD30 expression and staining pattern, prognostic indices using the International Prognostic Index and the Intergruppo Italiano Linfomi system, treatments, and clinical outcomes were examined. A sizeable proportion of 175 patients had a history of immune-related disorders (autoimmune 16%, viral infections 17%, chemo/radiotherapy-treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
5
3
0
Order By: Relevance
“…In agreement with previous studies, 19,21 our study found that achieving CR after frontline chemotherapy was significantly associated with more favorable outcomes. The COMPLETE study also confirmed that patients in CR1 had significantly longer OS and PFS and highlighted the potential significance of CR1 status for ASCT.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In agreement with previous studies, 19,21 our study found that achieving CR after frontline chemotherapy was significantly associated with more favorable outcomes. The COMPLETE study also confirmed that patients in CR1 had significantly longer OS and PFS and highlighted the potential significance of CR1 status for ASCT.…”
Section: Discussionsupporting
confidence: 93%
“…The median age at diagnosis across major subtypes was relatively lower in our study than that previously reported in western countries, 19–21 while similar to previous Chinese series 22,23 . Other clinical features of our patients were in keeping with other studies 19–21 . Consistent with other studies, AITL usually presented with aggressive clinical features, including advanced stage, B symptoms, elevated LDH and β2M, and higher IPI or PIT scores 6,21,24,25 .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations